Prevalence of Malaria Among Children Under Five Years of Age in Miya Ward Ganjuwa Local Government From 2013-2017 - Salisu, Umar Muhammad; Muhammad, Maimuna (THRIVE Health Science Journal, 2025)
The study was conducted from 2013 to 2017 in Miya ward Ganjuwa local government, Bauchi state, to ascertain the incidence of malaria in children aged 0 to 5. The majority of patients, particularly those under five, who visit the health facility in the Miya Ward clinic have been found to have malaria.  This is demonstrated by their epidemiological record, which was acquired at the health facility during the research project. The study project is anticipated to be important for the residents of the Miya ward clinic, especially the children under five, as well as for the government and non-governmental organizations to have a better understanding of the issues that are currently being faced.  Male children are more likely than female children to contract malaria, according to the results of this study, which was conducted using a descriptive research design in which data was collected using a methodical approach and the characteristics of specific variables related to the study were explained. Additionally, it was found that malaria is usually quite common during the rainy season.  Finally, more study should be done to determine the frequency of malaria in children throughout the whole Miya Ganjuwa local government in Bauchi state